Brainstem volume, diffusion, and metabolism are associated with chronic consciousness disorders after traumatic brain injury. Issue 2 (24th November 2022) - Sawamura, Shogo; Ikegame, Yuka; Kawasaki, Tomohiro; Nakayama, Noriyuki; Yano, Hirohito; Shinoda, Jun
Abstract: Background and Purpose: We aimed to identify reliable neuroradiological features of the brainstem reflecting the neurological symptoms of patients with chronic disorders of consciousness (DOCs) due to severe traumatic brain injury (TBI). Methods: We retrospectively examined 86 patients with chronic DOCs due to severe TBI caused by automobile accidents. We studied the relationships among (1) neurological symptoms, including consciousness level, (2) integrated cognitive/physical condition, and (3) neuroradiological features of the brainstem (brainstem volume on MRI, fractional anisotropy [FA] value in the brainstem, and standardized uptake value [SUV] of 18F‐fluorodeoxyglucose [FDG] on positron emission tomography in the brainstem). Results: Brainstem volume was significantly larger and FA values were significantly higher in patients with a better level of consciousness. However, brainstem volumes were significantly decreased and the maximum SUV (SUVmax ) of FDG significantly increased at 2 years following admission regardless of the level of consciousness at admission. The brainstem volume was significantly larger and the FA value and SUVmax of FDG were significantly higher in patients with better National Agency for Automotive Safety and Victims' Aid (NASVA) scores at admission. The decrease in the brainstem volume was significantly minimized and the SUVmax of FDG significantly increased in patients with more improvement in the NASVA score 2 years after admission. Conclusions: The volume, FA value, and SUVmax of FDG of the brainstem are important neuroradiological features associated with the neurological conditions of patients with chronic DOCs due to severe TBI.